2013
DOI: 10.1080/09571736.2013.833280
|View full text |Cite
|
Sign up to set email alerts
|

Using authentic picture books and illustrated books to improve L2 writing among 11-year-olds

Abstract: The case study investigates what impact extensive reading of authentic picture books/ illustrated books had on the learners' writing skills in a Norwegian EFL (English as a foreign language) classroom of 11-year-olds. Furthermore, the study also looks into the importance the pictures/illustrations had for the learners and what type of picturetext interaction they favoured. The case study was designed to allow the learners the freedom to choose for themselves, from a list provided, which books to read. The lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…According to the results presented in Table II analysis of covariance (pre-test), and Table III analysis of covariance (post-test), the hypothesis of this study was rejected. The findings of current study support some previous researches such as Zainal and Husin (2011), Lo and Hyland (2007), Kirin (2010), Al-Mansour andAl-Shorman (2014), Gupta andWoldemariam (2011), Al-Shourafa (2012), Lam and Law (2006), Hamidun et al (2012), Salehi et al (2015), and Birketveit and Rimmereide (2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to the results presented in Table II analysis of covariance (pre-test), and Table III analysis of covariance (post-test), the hypothesis of this study was rejected. The findings of current study support some previous researches such as Zainal and Husin (2011), Lo and Hyland (2007), Kirin (2010), Al-Mansour andAl-Shorman (2014), Gupta andWoldemariam (2011), Al-Shourafa (2012), Lam and Law (2006), Hamidun et al (2012), Salehi et al (2015), and Birketveit and Rimmereide (2013).…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the students need to be more active in educational communities. Furthermore, Birketveit and Rimmereide (2013) investigated "the impact of extensive reading through authentic picture books on the learners' writing skills." The study showed that the picture books improved learners' motivation to read and make progress in their writing performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, writing is often difficult for beginning writers (Camacho, & Alves, 2017), there is numerous educational intervention to improve the writing skills of children in primary school. Birketveit & Rimmereide, (2017) examined effects of general reading of dependable illustrated books/picture books had on the students' writing abilities in 11-year-olds EFL classroom. Limpo & Alves, (2017) investigated the mediating effect of pauses and bursts on the relation between text quality or writing fluency and transcription abilities.…”
Section: Treatments For Efl Young Children With Writing Disabilitiesmentioning
confidence: 99%
“…The included studies address the development of language in vocabulary (Al Darwish, 2015;Albaladejo Albaladejo et al, 2018;Birketveit & Rimmereide, 2017;Freire & Filho, 2015;Larragueta & Ceballos-Viro, 2018;Lin, 2014), reading (Al Darwish, 2015), and writing (Al Darwish, 2015;Birketveit & Rimmereide, 2017;Yeom, 2018). Vocabulary has received the most attention in terms of language skills developed by children's literature in the EFL classroom.…”
Section: Universidad De La Sabana Department Of Foreign Languages And...mentioning
confidence: 99%